2019
DOI: 10.1002/ecy.2917
|View full text |Cite
|
Sign up to set email alerts
|

Looking back to look ahead: a vision for soil denitrification research

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 52 publications
3
48
0
Order By: Relevance
“…Nevertheless, full denitrification is complicated, and might lead to additional N losses in form of N 2 O instead of N 2 . A comprehensive review by Almaraz et al (2020) showed that for a better understanding of how denitrification rates vary across the soil profile, there is a need to more precisely investigate ecosystem N budgets. Therefore, surface and subsoil measurements should be included in future studies to determine controls on denitrification in surface soils vs. subsoils [62].…”
Section: Effects Of Different Field Application Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, full denitrification is complicated, and might lead to additional N losses in form of N 2 O instead of N 2 . A comprehensive review by Almaraz et al (2020) showed that for a better understanding of how denitrification rates vary across the soil profile, there is a need to more precisely investigate ecosystem N budgets. Therefore, surface and subsoil measurements should be included in future studies to determine controls on denitrification in surface soils vs. subsoils [62].…”
Section: Effects Of Different Field Application Methodsmentioning
confidence: 99%
“…A comprehensive review by Almaraz et al (2020) showed that for a better understanding of how denitrification rates vary across the soil profile, there is a need to more precisely investigate ecosystem N budgets. Therefore, surface and subsoil measurements should be included in future studies to determine controls on denitrification in surface soils vs. subsoils [62]. Fangueiro et al [24] detected no N 2 O emission when slurry material was injected to 30 cm depth.…”
Section: Effects Of Different Field Application Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Denitrification, the microbial-mediated reduction of NO 3 − to di-nitrogen gas (N 2 ) under anaerobic conditions, is globally considered the primary biogeochemical process via which mineral N is returned to the atmosphere [10][11][12]. Whether N is denitrified and lost to atmosphere as N 2 or accumulates in the vadose zone and in groundwater [13,14] makes a huge difference in an environmental perspective and from the point of view of policymakers and stakeholders. Thus, assessing the fate of missing N is a major scientific challenge for defining codes of good agricultural practices and implementing effective management strategies aimed at protecting water quality in human-impacted watersheds.…”
Section: Introductionmentioning
confidence: 99%
“…This allows for comparison of all OM fractions across the different soils. Potential problems of the acetylene inhibition technique, i.e., underestimated N 2 production due to acetylene inhibition of nitrification and incomplete inhibition of N 2 O reduction caused by either low NO 3 − concentrations or acetylene diffusion effects (Knowles, 1990;Almaraz et al, 2020), can be excluded for the incubation conditions used (anoxic, excess NO 3 − , soil suspension).…”
Section: Incubation Gas Measurements and Calculationsmentioning
confidence: 99%